Pengaruh Serial Drama Bid’ah terhadap Persepsi Penonton tentang Patriarki di Era Modern: (Studi pada Mahasiswa Ilmu Komunikasi Universitas Bina Bangsa) - Mishelia Kartika Puspitasari; Noerma Kurnia Fajarwati; Meiby Zulfikar; Eka Susilawati; Rizqi Fitrianti (Pusat Riset dan Inovasi Nasional, 2026)
Patriarchy in the modern era still persists despite continuous efforts to achieve gender equality across various aspects of life, including education, the workplace, and social interactions. Its presence is often reinforced through mass media, particularly in television series. The drama series “Bid’ah” vividly portrays the impact of patriarchy on women’s lives, both in domestic settings and in the public sphere. This study aims to examine the extent to which exposure to the series “Bid’ah” influences viewers’ perceptions of patriarchy. This research employed a quantitative approach involving 100 undergraduate students from the Communication Science program at Universitas Bina Bangsa. The sampling technique used was purposive sampling, where participants were selected based on specific criteria relevant to the research objectives. Data were collected through an online questionnaire using a four-point Likert scale to measure the respondents’ perceptions. The data were then analyzed using simple linear regression with the help of SPSS software. The findings indicate a significant influence between exposure to the series and viewers’ perceptions of patriarchy. This is evidenced by a correlation coefficient of 0.405 (p-value 0.000) and a coefficient of determination of 0.164. These results suggest that 16.4% of the variance in perceptions of patriarchy can be explained by exposure to the “Bid’ah” series, while 83.6% is influenced by other factors beyond this study. These findings highlight the important role of media in shaping social perceptions, particularly regarding gender norms and patriarchal values. This study contributes to the understanding of how media, especially television dramas, can both reinforce and challenge gender stereotypes, while also providing insights into the potential influence of media content on audiences’ attitudes toward gender equality.